Revenue Mobilization through Tax: A Comparative Study of Bangladesh and Pakistan - Alam, Mohammad Faridul (AIUB Journal of Business and Economics, 2017)
This paper aims at analyzing and comparing the prevailing tax structure in Bangladesh and Pakistan in terms of their contribution to the economy. The study is based on tax data from 2005-2006 to 2014-2015. The results show that in both the countries Tax GDP ratio is one of the lowest among the SAARC countries. Considering the limited scope of direct taxes, revenue largely depends on indirect taxes like value added tax, customs duty, sales tax and excise tax. Contribution to indirect taxes to total revenue has an erratic trend. The study reflects the issue that tax evasion and avoidance, poor tax administration is the main problem of poor tax performance. But, Bangladesh and Pakistan have a very good opportunity to improve its tax performance by taking necessary reform measures.